Enforcement of the debt confirmed by the bank enforcement order by a bank that previously sold the debt by way of transfer to a securitization fund, as an example of unlawful activity resulting in unjustified enrichment on the part of the bank. An approvi - Kwaśniak, Aleksander (The Opole Studies in Administration and Law, 2021)
The subject of the commentary is the judgment of the District Court in Gdańsk, which dismissed the appeal brought by the bank against the judgment of the Court of first instance. This judgment ordered the bank to pay the consumer a sum of money for unjust enrichment, together with interest and litigation costs. As rightly stated by the courts of both instances, upon the transfer of the debt confirmed by the bank enforcement order by the bank to the entity other than the bank, the vendor of the claim should notify the enforcement bailiff of this fact with a request for its remission. The continuation of the enforcement constitutes an unlawful act of the bank, resulting in unjustified enrichment at the expense of the former debtor. Such an assessment is not changed by the fact that the bank transfers the enforced funds to the buyer of the debt, as the latter cannot benefit from the former, but should bring an action against the debtor for payment on general rules. The judgment deserves approval, and due to its practical dimension, also an in-depth commentary and dissemination.